Using Systematic Review and Evidence Banking to Increase Uptake and Use of Aquatic Science in Decision‐Making. (17th October 2018) - Bennett, Micah G.; Lee, Sylvia S.; Schofield, Kate A.; Ridley, Caroline; Norton, Susan B.; Webb, J. Angus; Nichols, Susan J.; Ogden, Ralph; Collins, Alexandra
Abstract: To support sound decision‐making in environmental management, we need rigorous, defensible, and transparent synthesis of scientific evidence. The Association for the Sciences of Limnology and Oceanography and associated aquatic science societies are leaders in applying science to decision‐making, and yet many environmental decisions are still at risk of having to be made without a comprehensive, well‐synthesized evidence base to support them. In this article, we discuss two synergistic approaches that can help science inform decision‐making: systematic review and evidence banking. Our aim is to promote the use of these approaches, and to enlist support and action from you, the aquatic science community. We propose that you can improve the use and uptake of science in decision‐making by making your research more compatible with synthesis efforts by: considering risk of bias when designing your study and reporting results; reporting all relevant contextual information; analyzing your data using standard effect size approaches; and publishing your raw data. Awareness of how primary research feeds into informing policies can help you broaden the impact of your research, making it more directly relevant to decision‐making and more likely to contribute to the protection of aquatic ecosystems.